Metasurface Array Illuminator Based on Fresnel Holography. (August 2020) - Mou, Zhen; Lu, Xiaoqing; Lv, Haoran; Han, Yuansheng; Yue, Qingyang; Wang, Shuyun; Teng, Shuyun
Highlights: The proposed metasurface array illuminators are designed on basis of Fresnel holography principle. The shape and layout of the light spots can be flexibly adjusted through changing the arrangement of rectangular holes of metasurface. Multispots generated with the help of metasurfaces have the characteristic of high density. Abstract: A kind of array illuminators is proposed based on optical metasurface consisting of rectangular nanoholes etched in silver film. The information of the metasurface hologram comes from the binarized Fresnel hologram of the target pattern. The light spot arrays are generated through the diffraction of the metasurface hologram under the right-handed circularly polarized light illumination. The shape and layout of the light spots can be adjusted through changing the arrangement of rectangular holes. The propagation distance of our array illuminator is set at 10μm. The advantages of the metasurface array illuminator including ultrathin thickness, compact structure, higher resolution and feasible fabrication are favorable to promote the applications of the metasurface holography in optical interconnection and optical integration.